2022
DOI: 10.3390/nano12193292
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of Rosmarinic Acid Using Peptide-Modified Graphene Oxide Screen-Printed Carbon Electrode

Abstract: Peptides have been used as components in biological analysis and fabrication of novel sensors due to several reasons, including well-known synthesis protocols, diverse structures, and acting as highly selective substrates for enzymes. Bio-conjugation strategies can provide a simple and efficient way to convert peptide-analyte interaction information into a measurable signal, which can be further used for the manufacture of new peptide-based biosensors. This paper describes the sensitive properties of a peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…Further preliminary analyses consisted of evaluating the electrochemical behavior of SPCE/GPHOX and SPCE/GPHOX-Pentapeptide in 0.1 M PBS at pH = 6.5. According to previous studies [ 23 , 60 , 61 ], the potential range in which a stable signal was obtained was from −0.4 to 1.0 V, proving to be optimal for the new peptide-based sensor described in the present study. The signal was stable after three cycles without interference or background noise, suggesting that there was no contamination of the active surface during the modification steps.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Further preliminary analyses consisted of evaluating the electrochemical behavior of SPCE/GPHOX and SPCE/GPHOX-Pentapeptide in 0.1 M PBS at pH = 6.5. According to previous studies [ 23 , 60 , 61 ], the potential range in which a stable signal was obtained was from −0.4 to 1.0 V, proving to be optimal for the new peptide-based sensor described in the present study. The signal was stable after three cycles without interference or background noise, suggesting that there was no contamination of the active surface during the modification steps.…”
Section: Resultssupporting
confidence: 57%
“…Taking into account our previous work [ 23 ], where it was demonstrated that the optimal pH value for electrochemical determinations at which a stable signal was obtained was 6.5, the determinations in this study were performed in solutions obtained by dissolving in 0.1 M PBS at pH 6.5. Moreover, in the same study, the optimal amount of peptide required for sensor modification was determined using different volumes of the peptide solution, demonstrating that the anodic peak was more intense and better defined when using a volume of 20 µL [ 23 ]. Therefore, the same volume of 20 µL of the pentapeptide solution was also used in the present study to obtain the modified sensor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, GO as a certain nanoarchitectonics, has been widely used by providing functional groups as active sites to connect small organic molecules, polymers, and other functional groups [ 20 , 21 , 22 , 23 , 24 ]. It has been used in applications relating to pharmaceutical carriers [ 24 , 25 , 26 ], the biological environment [ 27 , 28 ], energy fields [ 29 , 30 ], and nanoelectronics and optoelectronics [ 31 , 32 , 33 , 34 , 35 , 36 ], etc.…”
Section: Introductionmentioning
confidence: 99%